On some estimates of singular number of integral operator of Hilbert-Schmidt - Radzievska, Elena (My University, 2013)
Establish estimates for the singular values through the modulus of continuity of the kernel of integral operator.Отримані оцінки для сингулярних чисел через модулі неперервності ядра інтегрального оператора.
Keywords: singular values of the moduli of continuity; the integral operator; модулі неперервності; інтегральний оператор; сингулярні числа; кафедра вищої математики імені проф. Можара В. І.